COVID-19: Considerations for Children and Families During the Pandemic - Binzhi Tang; Binzhi Tang; Binzhi Tang; Didarul Alam; Mejbah Uddin Rakib; Maojun Li; Maojun Li (Frontiers Media S.A., 2021)
Coronavirus disease 2019 (COVID-19), a fatal virus caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a pandemic across the world. Despite early concerns, children appear to be less susceptible to acquiring SARS-CoV-2 and manifest minor clinical symptoms compared with adults. However, there still exists a risk of physical and psychological health problems in children and their families. In this review, we summarize the existing information about the mechanism of SARS-CoV-2 infection, the epidemiology of COVID-19, and the clinical manifestations, treatments, and further considerations regarding COVID-19 in children.